Percutaneous nephrolithotomy for renal stones combined with laser endoscopy for ipsilateral renal cysts: a case report and literature review - Li, Shuxin; Wang, Fulin; Cao, Hongliang; Zhang, Yueqiu; Wang, Binbin; Huang, Gengchen; Wei, Wei (Frontiers in Surgery, 2025)
Renal cysts and renal stones are common diseases in urology, but it is less common for both to coexist in a patient's kidney. In some unsophisticated urology clinics, separate elective treatments for renal cysts and renal stones are usually chosen, reducing the surgery risk but increasing the financial burden for patients. In this paper, we report a case of percutaneous nephrolithotomy for managing renal stones and endoscopy of renal cysts. The patient was a 61-year-old woman with back pain for more than 10 days. She was preoperatively diagnosed with left kidney stones and bilateral renal cysts. The patient underwent percutaneous nephrolithotomy with laser lithotripsy for left kidney stones and end cystectomy for left kidney cysts, with an indwelling ureteral stent and nephrostomy tube. The patient's back pain subsided postoperatively, and he was discharged on the 5th postoperative day. The nephrostomy tube was removed 1 week after surgery, and the ureteral stent was removed 1 month after surgery. The purpose of this case is to demonstrate to surgeons the advantages of percutaneous nephrolithotomy laser lithotripsy for treating renal stones combined with intrarenal cysts. Suppose a kidney stone is adjacent to a renal cyst, for example. In that case, if the stone is located adjacent to the renal pelvis or near the calyx in which the stone is located, percutaneous nephrolithotomy laser lithotripsy can treat both conditions.